PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN AKRUAL TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014) - Nissa Arisanty Pratita Arisanty Pratita; Zirman Zirman; Lila Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research to examined the Effect of Tax Planning, Deffered Tax Expense and Acruals on the of earnings management. The object of research is the manufacturing companies registered on the Indonesia Stock Exchange (IDX) the observation period of 2012-2014. The data used in thhis research is based on annual financial reports obtained through the site www.idx.co.id. The sampling method use purposive sampling. The are 43 samples to be analyse use multiple regression with the help of SPSS software versi 17.0. The results of this study indicate that the variable tax planning has a value of research tax planning, deffered tax expense and accrual have positive effect on earning management. Simultaneous regression test (F-test) showed that all dependent variable have significant influence to the dependent variable. Donations effect of tax planning, deffered tax expense and accruals on the earnings management with empirical studies in the manufacturing companies registered on the Indonesia Stock Exchange with coefficient determination (R2 )by 34.3%. 65,7% while the rest describe other independent variables that are not observed in this study.Keywords : Tax Planning, Deffered Tax Expense, Accruals and Earnings Management.